1976
DOI: 10.1002/jlac.197619761105
|View full text |Cite
|
Sign up to set email alerts
|

Verfahren zur Darstellung von 4‐Oxo‐1,4‐dihydropyridincarbonsäurederivaten

Abstract: Durch basenkatalysierte, intramolekulare Kondensation der Michaeladdukte 1 aus homooder heteroaroniatischen o-Aminocarbonsaureestern und AcetylendicarbonsLureestern werden aromatisch anellierte 4-0~0-1,4-dihydr0-2,3-pyridindicarbonsaureester 2 erhalten. Diese konnen durch regioselektive Verseifung und Decarboxylierung in die entsprechenden 443x0-1,4-dihydr0-3-pyridincarbonsauren umgewandelt werden.A General Synthesis of 4-0x0-I ,4-dihydropyridinecarboxylic Acid Derivatives Homo-or heteroaromatically annelated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Unfortunately, methyl 3-(trimethylsilyl)propiolate (Z ) TMS) did not undergo any vinylonio reaction. Yet, as the decarboxylation of quinolones of type 32 at C2 is known from the literature to be simple and highly effective, 12 the above-mentioned method provides a novel synthetic approach to modern fluoroquinolone antibiotics (which bear a hydrogen substituent at C2 as well as a carboxy group at C3). These constitute the most important class of antiobiotics used today, curing a wide variety of diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, methyl 3-(trimethylsilyl)propiolate (Z ) TMS) did not undergo any vinylonio reaction. Yet, as the decarboxylation of quinolones of type 32 at C2 is known from the literature to be simple and highly effective, 12 the above-mentioned method provides a novel synthetic approach to modern fluoroquinolone antibiotics (which bear a hydrogen substituent at C2 as well as a carboxy group at C3). These constitute the most important class of antiobiotics used today, curing a wide variety of diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Analogously to the three-step synthesis of 1, from methyl 2-aminobenzoate (5.0 mmol) (see also [38] (7)). Analogously to the three-step synthesis of 4, from methyl 5-hydroxy-2-aminobenzoate (1.6 mmol).…”
Section: Experimental Partmentioning
confidence: 99%
“…Antimicrobial 4(1H)-quinolones norfloxacin (Norfluxx ® ) and ciprofloxacin (Ciprobay ® ) Classic syntheses of 4(1H)-quinolones rely on the addition of (ethoxymethylene)malonates with anilines and subsequent cyclization 8 and on the addition of maleates to o-aminobenzoates and subsequent cyclization. 9 However, these methods are not suitable for the synthesis of 2,3-un-substituted 4(1H)-quinolones as the ester groups present at these positions have to be removed in several steps. Heindel et al reported 10 and elegant approach to 4(1H)quinolones by nucleophilic addition of anilines to methyl acetylenecarboxylate and subsequent cyclization.…”
Section: Figurementioning
confidence: 99%